Chemical Sensing Systems that Utilize Soft Electronics on Thin Elastomeric Substrates with Open Cellular Designs. (9th January 2017) - Lee, Yoon Kyeung; Jang, Kyung‐In; Ma, Yinji; Koh, Ahyeon; Chen, Hang; Jung, Han Na; Kim, Yerim; Kwak, Jean Won; Wang, Liang; Xue, Yeguang; Yang, Yiyuan; Tian, Wenlong; et al.
Abstract : A collection of materials and device architectures are introduced for thin, stretchable arrays of ion sensors that mount on open cellular substrates to facilitate solution exchange for use in biointegrated electronics. The results include integration strategies and studies of fundamental characteristics in chemical sensing and mechanical response. The latter involves experimental measurements and theoretical simulations that establish important considerations in the design of low modulus, stretchable properties in cellular substrates, and in the realization of advanced capabilities in spatiotemporal mapping of chemicals' gradients. As the chemical composition of extracellular fluids contains valuable information related to biological function, the concepts introduced here have potential utility across a range of skin‐ and internal‐organ‐integrated electronics where soft mechanics, fluidic permeability, and advanced chemical sensing capabilities are key requirements. Abstract : A collection of materials and device architectures are introduced for thin, stretchable arrays of ion sensors that mount on open cellular substrates to facilitate solution exchange for use in biointegrated electronics. As the chemical composition of extracellular fluids contains valuable information related to biological function, the concepts and the integration/design strategies introduced here have potential utility across a range of skin‐ and other organ‐integrated electronics where soft mechanics, fluidic permeability, and advanced chemical sensing capabilities are key requirements.